PERSISTENT VOMITING AS THE PRESENTATION OF THYROTOXICOSIS: A CASE REPORT - Tong, Chin Voon (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Thyrotoxicosis may have many different presentations at diagnosis. We present a case of thyrotoxicosis with the presentation of only recurrent vomiting in pregnancy. CASE The patient’s medical records were traced and reviewed. A 41-year-old Malay female, G4P2 with one miscarriage, with underlying type 2 DM initially presented during pregnancy with recurrent admissions for vomiting since the first trimester. She was admitted and treated for hyperemesis gravidarum and urinary tract infection at 12 and 14 weeks gestation. She was readmitted at 28 weeks for recurrent vomiting and reduced oral intake one week prior to admission. She denied having conventional symptoms of thyrotoxicosis. She did not have any family history of thyroid disorder. Examination findings revealed a small goitre with no fine tremors or thyroid eye signs, BP within normal range and HR 100 to 107. Clinically, she had mild dehydration. Multiple investigations including serum calcium, ketone, amylase and brain MRI to look for the cause of persistent vomiting were normal. During her third admission, thyroid tests were done for evaluation of tachycardia. Results showed elevated FT4 (66 pmol/L), suppressed TSH (0.01mIU/L), negative thyroid antibodies and no significant abnormality on neck ultrasonography. She was started on oral carbimazole 20 mg OD and oral propranolol 20 mg BD. Vomiting was resolved thereafter. She delivered via emergency lower caesarean section at 31 weeks for abnormal cardiotocography and foetal intrauterine growth restriction. CONCLUSION Recurrent vomiting in pregnancy is a rare presentation for thyrotoxicosis. This should not be missed in clinical practice to prevent adverse maternal and foetal outcomes.